Operating windows for early evaluation of the applicability of advanced reactive distillation technologies - Pazmiño-Mayorga, Isabel; Jobson, Megan; Kiss, Anton A. (Chemical engineering research & design, 2023)
Advanced reactive distillation technologies (ARDT) are often overlooked during process synthesis due to their complexity. This work proposes the use of operating windows with additional features to identify suitable operating limits for ARDT. Data needed to construct the operating windows are thermodynamic properties, kinetic parameters, constraints of materials and experimental methods, and heuristics. In addition, two new concepts are proposed to represent complex features: representative components and a sliding window. Results include the identification of suitable operating limits for ARDT to help assess their feasibility early in process design. The proposed approach is demonstrated by case studies. Methyl acetate production can be carried out at low pressures (0.5–3.6 atm), while lactic acid purification requires vacuum conditions (0.3–0.8 atm) to avoid thermal degradation. Tert-amyl methyl ether production was evaluated in two scenarios where the effect of side reactions is evidenced in a reduction of the reaction window due temperature limits to favour the main reaction over side reaction. This study is the first to evaluate advanced reactive distillation technologies using a graphical representation in an operating window to aid process synthesis, where the results provide key selection insights. •Process intensification enabled via advanced reactive distillation technologies.•Operating windows construction to expand the applicability of reactive distillation.•Simplification strategies to represent multicomponent systems in operating windows.